El tráfico ilegal de seres humanos para la explotación sexual y laboral: la esclavitud del siglo XXI - Anguita Olmedo, Concepción (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
In our days, the organized crime is a phenomenon that affects the globalized international society becoming a specific object of International Relations. Organized crime summarizes a great diversity of lawbreakings –illegal inmigration, laundering of money, sexual trafficking, labor exploitation, drug dealing and arms trade- whose dimension has encouraged not only its conceptualization, but also the political performance in the state and supranational areas. This study is structured on the equation between illegal immigration and sexual and labor trafficking, since this kind of trafficking has become the second more lucrative criminal business after drug dealing. Its international implications, prevention and repression policies and its repercussion in the developing countries as well as its impact on the trafficked persons are the main subject of this work.